The Influence Of Self-Efficacy And Social Support Toward Self-Regulation On Traditional Dancers - Agia Rahmah; Gazi Gazi (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2017)
Dancers often feel things that could affect the movement of a dance as on when we get emotion dancer disturbances often unstable, a lack of concentration when dancers perform thus reducing penghayatan to motion in a dance and the importance of a proper partnership between dancer (if in one team). Penelitian aims to understand is there the influence of self-efficacy (initiative, Effort, and persistence) and social support (guidance, reassurance of worth, social integration, attachment , nurturance, and reliable alliance) against regulations themselves and traditional dancers. This study using methods of multiple regression analysis as the proportion of respondents as many as 201 members of traditional dance studio. A measuring instrument used was the self-regulation questionnaire, general self-efficacy scale (gses-12), the social provision scale. The results of the hypothesis minor show a variable that has the influence of a significant impact on regulations self is effort, reassurance of worth, social integration, attachment, and nurturance. Penari sering merasakan hal-hal yang dapat mempengaruhi gerakan dari sebuah tarian seperti pada saat tampil gejolak emosi penari sering tidak stabil, kurangnya konsentrasi penari disaat tampil sehingga mengurangi penghayatan terhadap gerakan dalam sebuah tarian dan pentingnya kerjasama yang baik antar penari (jika dalam satu tim). Penelitian ini bertujuan untuk mengetahui apakah ada pengaruh self efficacy (initiative, effort, dan persistence) dan dukungan sosial (guidance, reassurance of worth, social integration, attachment, nurturance, dan reliable alliance) terhadap regulasi diri penari tradisonal. Penelitian ini menggunakan metode multiple regression analysis dengan responden sebanyak 201 anggota sanggar tari tradisional. Alat ukur yang digunakan adalah The self regulation questionnaire, General self efficacy scale (GSES-12), The social provision scale. Hasil uji hipotesis minor menunjukkan variabel yang memiliki pengaruh yang signifikan terhadap regulasi diri ialah effort, reassurance of worth, social integration, attachment, dan nurturance. DOI: 10.15408/jp3i.v6i1.8146